Welcome! : English for the travel and tourism industry : teacher's book - Jones, Leo. (Cambridge University Press, 1998)
Different kinds of people. International travel. Phone calls. Food and drink. Letters and faxes. Accomodation. Money. Travelling around. Problems. Attractions and activities.